Cholinesterase from the liver of Diodon hystrix for detection of metal ions - Nordin, Noreen; Cletus, Ronaldo Ron; Sabullah, Mohd Khalizan; Muhammad Khalidi, Siti Aishah; Abdulla, Rahmath; Ahmad, Siti Aqlima (Universiti Putra Malaysia Press, 2020)
The discharge of industrial effluents into nearby water bodies affects the inhabitants including living organisms. The presence of foreign materials such as heavy metals can be a threat to the ecosystem as they are enormously carcinogenic even though in minute concentration. Hence, an economical and time-efficient preliminary screening test is crucial to be developed for the detection of heavy metals, prior to employment of high technology instruments. In this study, cholinesterase (ChE) from Sabah porcupine fish, Diodon hystrix was purified to test for its potential as an alternative biosensor in detecting metal ions. Few enzymatic parameters including specificity of substrate, temperature and pH were applied to determine its optimal enzymatic activity. ChE enzyme was found to be more sensitive towards the presence of substrate, butyrylthiocholine iodide (BTC), in contrast to acetylthiocholine iodide (ATC) and propionylthiocholine iodide (PTC) with the effective coefficient at 7193, 3680.15 and 2965.26 Vmax/Km, respectively. Moreover, the extracted ChE enzyme showed the optimum activity at pH 9 of 0.1 M Tris-HCl and at 25°C to 30°C range of temperature. When subjected to heavy metals, ChE enzyme was significantly inhibited as the enzyme activity was reduced in the sequence of Hg > Ag > Cr > Cu > Cd > Pb ≥ Zn > As. As a conclusion, the partially purified ChE enzyme proved its sensitivity towards metal ion exposure and can be used as an alternative method in screening the level of contamination in the environment.